(untitled) (Fiep Bulletin - online, 2016)
Often called the Brazil Volleyball and Portugal’s Volleyball is a sport played on a court divided into two parts by a network, having two teams of six players on each side. The aim of the game is to pass the ball over the net so that it touches the ground within the opponent’s court at the same time it prevents the opponents are able to do the same. Volleyball is an Olympic sport governed by the Fédération Internationale de Volleyball (FIVB). The volleyball was invented on 9 February of 1895 by William George Morgan in the United States of America. The aim of Morgan, who worked at the Holyoke YMCA in Massachusetts, was to create a sports teams without physical contact between the opponents in order to minimize the risk of injury. Initially played with a tube basketball ball and was called Mintonette, but quickly gained popularity with the name of volleyball. Volleyball creator died on December 27, 1942 at 72 years old. A team that want to compete at the international level need to master a set of six basic skills, usually called under "fundamentals." They are: serve, pass, lifting, attack, block and defense. Each of those pleas comprises a number of skills and techniques that have been introduced over the history of volleyball and are now considered common practice in the sport.